Inhibition of interleukin‐1β production by extracellular acidification through the TDAG8/cAMP pathway in mouse microglia. (10th February 2014) - Jin, Ye; Sato, Koichi; Tobo, Ayaka; Mogi, Chihiro; Tobo, Masayuki; Murata, Naoya; Ishii, Satoshi; Im, Dong‐Soon; Okajima, Fumikazu
Abstract Interleukin‐1β (IL‐1β) is released from activated microglia and involved in the neurodegeneration of acute and chronic brain disorders, such as stroke and Alzheimer's disease, in which extracellular acidification has been shown to occur. Here, we examined the extracellular acidic pH regulation of IL‐1β production, especially focusing on TDAG8, a major proton‐sensing G‐protein‐coupled receptor, in mouse microglia. Extracellular acidification inhibited lipopolysaccharide ‐induced IL‐1β production, which was associated with the inhibition of IL‐1β cytoplasmic precursor and mRNA expression. The IL‐1β mRNA and protein responses were significantly, though not completely, attenuated in microglia derived from TDAG8‐deficient mice compared with those from wild‐type mice. The acidic pH also stimulated cellular cAMP accumulation, which was completely inhibited by TDAG8 deficiency. Forskolin and a cAMP derivative, which specifically stimulates protein kinase A (PKA), mimicked the proton actions, and PKA inhibitors reversed the acidic pH‐induced IL‐1β mRNA expression. The acidic pH‐induced inhibitory IL‐1β responses were accompanied by the inhibition of extracellular signal‐related kinase and c‐Jun N‐terminal kinase activities. The inhibitory enzyme activities in response to acidic pH were reversed by the PKA inhibitor and TDAG8 deficiency. We conclude that extracellular acidic pH inhibits lipopolysaccharide‐induced IL‐1β production, at least partly, through the TDAG8/cAMP/PKA pathway, by inhibiting extracellular signal‐related kinase and c‐Jun N‐terminal kinase activities, in mouse microglia. <boxed-text content-type="graphic" id="jnc12661-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> A number of studies have shown that extracellular acidification in brain is observed in ischemia and neurodegenerative disorders. However, the molecular mechanism by which extracellular acidification regulates the biological activities of microglia remains uncharacterized. Here, we examined the extracellular acidic pH regulation of IL‐1β production, especially focusing on TDAG8, a member of OGR1 family receptors. Our results suggest that extracellular acidic pH inhibited lipopolysaccharide ‐induced IL‐1β production at least partly through the TDAG8/cAMP pathway, by inhibiting ERK and JNK activities.